O discurso da Nova Escola : procedimentos e valores - Castro, Juliana Contti (2013)
This work examines the construction of the pedagogic discourse in the Nova Escola (New School) magazine, the discoursive procedures utilized in this construction, and the framework of values in which these discourses insert themselves. Thus this work takes as the principle corpus of analysis the periods 1997-1998 and 2011-2012. Emphasizing the analysis of the magazine s editorials, covers and advertisements, this work investigates the effects of meaning that these texts produce based on its discoursive construction. For the description and analysis of the verbal-visual texts, it refers to the French semiotic and its model of analysis of the signification proposed by A. J. Greimas, together with the visual semiotic, with the contributions of J. M. Floch. Its objectives are to design a landscape about the emergence of the magazines and their similarity to the newspaper; to localize the emergence of the Brazilian pedagogic publications; to investigate the emergence and consolidation of the Editora Abril as an expressive communication company; to examine the creation of the Victor Civita Foundation and, lastly, to investigate the teacher simulacrum reiterated and strengthened by the discourse of Nova Escola (New School). The analysis points to the reinforcement of a simulacrum that sees education, specially the first two years, as vocation and mission, stressing the instrumental dimension at the expense of the conceptual. The gender questions are also important; above all by the fact of the woman-teacher simulacrum be continuously reiterated in the discourse of the refered media. In terms of discoursive procedures, the play between objectivity and subjectivity, reinforces the scientific discourse as well as the relation of approximation that the magazine establishes with its readers. Thus, this work verifies the absence of any lexeme that treats the associative and sindical questions related to the teaching profession. The reiteration of the red, in what refers to the visual aspects, and the passionate feature of the texts highlights the verbal-visual discourse of Nova Escola, intrinsically connected to the reinforcement of the love-dedication-education relation.